A Review Article on an Appraisal of Maritime Laws as a Mechanism of Community Governance for Sustainable Development Goals - Hussain, Mazhar; Bhatti, Shaukat Hussain (Pakistan Journal of Humanities and Social Sciences, 2023)
As a result of the world's reliance on the blue economy, approximately 80 to 90% of commerce is marine; we cannot lament the Maritime’s interlinking associations with joint stability, social governance, and sustainable development, even in the least environment. There are robust links between maritime laws and community governance. These relationships are concerned with both socioeconomic and sociopolitical stability. Despite regular legislation to protect marine interests, challenges still need to be solved, which can only be accomplished via collaborative governance subject to maritime security. It is well-known that the blue economy, closely related to marine safety, is a source for assuring economic strength. This research aims to conduct a descriptive evaluation using a qualitative technique to highlight the concerns and challenges of naval legislation involving social control. This review will explicitly discuss the possible measures to overcome and eradicate the existing flaws by making suggestions to ensure communal management for desired outcomes regarding sustainable development goals, as well as strapping and long-term improvement of the socioeconomic and sociopolitical affairs between the states. This research will also discuss potential measurements and methods for determining desirable results for present requirements and future demands for altering Pakistani society to achieve long-term development objectives.